MERETAS PROBLEMATIKA ARAH KIBLAT TERKAIT SALAT DI ATAS KENDARAAN - Wakia, Nurul; HR, Sabriadi (UIN ALAUDDIN MAKASSAR, 2020)
The focus of this paper is to solve the problem of Qibla direction which related to prayers on vehicle. This paper was library research which the data were collected through review of written documents and online data and described through descriptive qualitative. In Islamic law the Qiblahdirection is stipulated as one of condition for the prayers validity.It is an obligation for Muslims in to pray facing the Ka’bah wherever in any under circumstances. The Muslim scholar agree that it is an obligation to face the Ka’bah for the people who can see it directly (‘Ainul Ka’bah) and an obligation to face the Ka’bah (Jihatul Ka’bah) for the people who cannot see it directly. When travelling and on a vehicle it is an obligation to pray facing the Qiblah, but if it not possible to do the fardhu prayer on a vehicle, it must be repeated when it reaches the permanent place. However, if it is only sunnah prayer it may be carried out on the vehicle without repeating it. Keywords: Qibla direction, prayers, on vehicle